Estuarine feeding by Lapwings Venellus vanellus and Golden Plovers Pluvialis apricaria - Mason, C F; Macdonald, S M (Wildfowl, 1999)
Preliminary observations are presented on intertidal feeding by Lapwings and Golden Plovers in eastern England. It is considered that the use of estuaries for foraging may be more prevalent than is realised. Warmer autumns resulting from global warming may make traditional feeding areas in cereal fields unsuitable due to rapid crop growth. More systematic data on estuarine feeding are required to determine if this a developing habit.